2017
DOI: 10.1039/c7ra06429b
|View full text |Cite
|
Sign up to set email alerts
|

Reversible structural phase transition, ferroelectric and switchable dielectric properties of an adduct molecule of hexamethylenetetramine ferrocene carboxylic acid

Abstract: Metallo-organic molecules showing reversible structural phase transitions accompanied with ferroelectric and dielectric properties have seldom been reported. By making use of the "driving/controlling force" from the rotating motion of cyclopentadienyl rings for a reversible structural transition and then carrying out structural modifications on their local parts to create remnant polarization through this molecular system, we designed and constructed a new ferroelectric, which is the adduct of hexamethylenetet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 32 publications
(15 reference statements)
1
10
0
Order By: Relevance
“…Metal‐free three‐dimensional perovskite ferroelectrics has been reported . In addition, there are some molecular ferroelectrics with excellent switchable dielectric properties, such as (CHA) 2 CdCl 4 , hexamethylenetetramine ferrocene carboxylic acid, hexamethylene‐tetramine bisnopinic acid, dabco⋅p‐nitrophenol, and so on. Recently, a number of pyridyl‐based molecular ferroelectrics have been discovered, such as PyX (Py =pyridinium and X = ClO 4 , BF 4 , ReO 4 , IO 4 ), (4‐amino‐2‐bromopyridinium) (4‐amino‐2‐bromopyridine) tetrafluoroborate, pyridin‐4‐ylmethanaminium perchlorate, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Metal‐free three‐dimensional perovskite ferroelectrics has been reported . In addition, there are some molecular ferroelectrics with excellent switchable dielectric properties, such as (CHA) 2 CdCl 4 , hexamethylenetetramine ferrocene carboxylic acid, hexamethylene‐tetramine bisnopinic acid, dabco⋅p‐nitrophenol, and so on. Recently, a number of pyridyl‐based molecular ferroelectrics have been discovered, such as PyX (Py =pyridinium and X = ClO 4 , BF 4 , ReO 4 , IO 4 ), (4‐amino‐2‐bromopyridinium) (4‐amino‐2‐bromopyridine) tetrafluoroborate, pyridin‐4‐ylmethanaminium perchlorate, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…discovered that Rochelle salt derivatives, bis(imidazolium) l ‐tartrate is a new organic H‐bonded molecular ferroelectric material, where imidazole acts as a classical molecular rotator and l ‐tartaric acid as homochiral component . Moreover, by means of twist motion of two cyclopentadienyl rings in ferrocene for a reversible phase transition, our group also explored a new ferrocene derives, adduct of hexamethylenetetramine ferrocene carboxylic acid which displays ferroelectricity . These successful strategies show that some derivatives of molecule ferroelectrics such as the organic salts and neutral adducts are possibility of becoming new type of ferroelectrics.…”
Section: Introductionmentioning
confidence: 99%
“…Generally speaking, the cocrystals fall into two categories; those made of inorganic‐organic components, and those made of pure organic components . They were all reported to possess switchable dielectrics , . Recently, an inorganic‐organic co‐crystal (Me 3 NH) 4 [Ni(NCS) 6 ] was studied by Jing‐Yan Liu et al, and it was reported that it undergoes an isostructural order‐disorder phase transition and it can function as a frequency‐tuned dielectric switch with highly adjustable switch temperature .…”
Section: Introductionmentioning
confidence: 99%
“…A well‐known case is the class of organic amine and organic acid cocrystals with the formula [A][B] or [A] 2 [B] (where, A = organic acid and B = organic amine, dabco, etc. ), where the ammonium cations in these structures make it very easy to achieve order‐disorder transitions around the phase transition temperature with obvious switchable dielectric anomalies . Horiuch i et al reported the ferroelectric organic solids, the cocrystals of 1:1 phenazine with chloranilic acid and bromanilic acid .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation